BLOOD CLOTTING NUMERICAL SIMULATION - E. M. Lashkevich; V. M. Bondarik (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of the blood clotting numerical simulation are shown. The work of the «Hemostasis» software tool are considered. The principal possibilities for numerical experiments are specified.